Prevalence of the E321G MYH1 variant for immune‐mediated myositis and nonexertional rhabdomyolysis in performance subgroups of American Quarter Horses. (8th January 2019) - Gianino, Giuliana M.; Valberg, Stephanie J.; Perumbakkam, Sudeep; Henry, Marisa L.; Gardner, Keri; Penedo, Cecilia; Finno, Carrie J.
Abstract : Background: Immune‐mediated myositis (IMM) in American Quarter Horses (QHs) causes acute muscle atrophy and lymphocytic infiltration of myofibers. Recently, an E321G mutation in a highly conserved region of the myosin heavy chain 1 ( MYH1 ) gene was associated with susceptibility to IMM and nonexertional rhabdomyolysis. Objectives: To estimate prevalence of the E321G MYH1 variant in the QH breed and performance subgroups. Animals: Three‐hundred seven elite performance QHs and 146 random registered QH controls. Methods: Prospective genetic survey. Elite QHs from barrel racing, cutting, halter, racing, reining, Western Pleasure, and working cow disciplines and randomly selected registered QHs were genotyped for the E321G MYH1 variant and allele frequencies were calculated. Results: The E321G MYH1 variant allele frequency was 0.034 ± 0.011 in the general QH population (6.8% of individuals in the breed) and the highest among the reining (0.135 ± 0.040; 24.3% of reiners), working cow (0.085 ± 0.031), and halter (0.080 ± 0.027) performance subgroups. The E321G MYH1 variant was present in cutting (0.044 ± 0.022) and Western Pleasure (0.021 ± 0.015) QHs at lower frequency and was not observed in barrel racing or racing QHs. Conclusions and Clinical Importance: Knowing that reining and working cow QHs have the highest prevalence of the E321G MYH1 variant and that the variant is more prevalent than the alleles for hereditary equine regional dermal asthenia and hyperkalemic periodic paralysis in the general QH population will guide the use of genetic testing for diagnostic and breeding purposes.